Adapting Palliative Care Skills to Provide Substance Use Disorder Treatment to Patients With Serious Illness. (January 2022) - Jones, Katie Fitzgerald; Ho, J. Janet; Sager, Zachary; Childers, Julie; Merlin, Jessica
Background: The majority of Palliative Care (PC) clinicians report recently caring for a person with a Substance Use Disorder (SUD). The impact of an untreated SUD is associated with significant suffering but many PC clinicians report a lack of confidence in managing this population. Objective: This paper aims to demonstrate existing PC skills that can be adapted to provide primary SUD treatment. Methods: A comprehensive literature review was conducted on quality PC domains and core SUD treatment principles. To demonstrate the shared philosophy and skills of PC clinicians and SUD treatment, the National Consensus Project Clinical Practice Guidelines for Quality Palliative Care and resources outlining core Addiction Medicine and Nursing Competencies were used. Results: There is an abundance of overlapping domains in PC and SUD treatment. This paper focuses on the domains of communication, team-based care, quality of life considerations, addressing social determinants of health, and adherence to ethical principles. In each section, the shared domain in PC and SUD treatment is discussed and steps to expand PC clinician's skills are provided. Conclusion: PC clinicians may be among the last healthcare touchpoint for persons with SUD, by naming the shared skills required in PC and evidenced-based SUD treatment, we challenge the field to undertake primary SUD treatment as part of its constant pursuit to better serve people living with serious illness.